ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN DAN LOYALITAS PESERTA BPJS KESEHATAN DI RSUD ARIFIN ACHMAD PEKANBARU - Wibowo, Anom Adi; Alwie, Alvi Furwanti (Jurnal Tepak Manajemen Bisnis, 2017)
This study aimed to analyze the influence of the quality of service to clientsatisfaction BPJS kesehan participants and to analyze the influence of satisfaction onloyalty participants in the health BPJS Arifin Achmad Pekanbaru. Analyses were basedon 121 patient samples BPJS participant health. While the sampling method usedprobability sampling and techniques used in this sampling is the sampling area.Collecting data using questionnaires and then the results statements from respondentswere processed and analyzed the quality layana on satisfaction and loyalty of patientswith hypothesis testing.The results showed that the quality of services simultaneously significant effect onpatient satisfaction in the health BPJS Arifin Achmad Pekanbaru. Partially, the qualityof services that have a significant effect only two variables, reliability andresponsiveness. While variable tangibles, assurance and empathy no significant effecton patient satisfaction health BPJS participants. Furthermore, namely the satisfactionsignificantly influence patient loyalty health BPJS participants at Arifin AchmadPekanbaru.